Efektivitas Asesmen Terpadu dalam Menentukan Rehabilitasi bagi Penyalahguna Narkotika di BNN Kota Palangka Raya - Judius Syahpala Sidauruk; Kiki Kristanto; Rizki Setyobowo Sangalang; Vicka Prama Wulandari (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the effectiveness of the Integrated Assessment implementation in determining the eligibility for rehabilitation of drug abusers at the Palangka Raya City National Narcotics Agency (BNN), as well as to identify strategies to overcome various operational obstacles in the field. The research method used is empirical juridical with a descriptive qualitative approach. The results indicate that during 2024, 124 clients underwent drug rehabilitation. The assessment was conducted through medical examinations and legal analysis to determine the offender's status and support a restorative justice approach. Despite obstacles such as limited budget, facilities and inter-agency coordination, the Palangka Raya City BNN continues to make improvements through crossagency collaboration and the use of communication technology.